Reklasifikasi Peta Penutupan Lahan untuk Meningkatkan Akurasi Kerentanan Lahan - Endang Savitri; Irfan Budi Pramono (Department of Urban and Regional Planning, Diponegoro University, 2017)
Land vulnerability is an important information to formulate land rehabilitation activities since it indicates the response of that particular land to erosion. It was determined by several factors such as slope, soil types, rainfall, and land cover. The land cover could be managed to maintain the land vulnerability. Inaccuracies of land cover classification would produce different vulnerabilities, which can cause miscalculation in land rehabilitation planning and implementation. This research is to adjust the existing land cover classification in order to detect land vulnerabilities. The analysis is done by comparing the classification of the existing land cover map with land cover criteria for land vulnerability analysis. The classification result then overlayed with land system map to determine the land vulnerability. The result of a study in Cisadane watershed shows that inaccuracy in determining unirrigated farming into shrub land or moor/open field could affect the shifting of vulnerable class to very vulnerable. Differences in determining plantations and unplanted estate areas with open field could also raise the extent of land vulnerability to 12.3%. Settlement in an urban area that turned into buildings would reduce the level of land vulnerability to 2.1%. Buildings could reduce the land vulnerability due to the impermeable layer would decrease erosion. However, from the hydrological point of view, the impermeable layers would increase the hydrological vulnerability due to the increased runoff and reduced ability to absorb water. Land cover data selection as input to determine the land vulnerability is very important and sensitive. For that reason, in the Cisadane Watershed, dryland farming should be classified as open field and settlement in urban areas should classify as buildings.